The level of TQM practices in tertiary education industry - Romle, Abd Rahim; Mohd Rodzi, Safarina; Kamal Ideris, Muhamad Shah; Saberi, Nasarina; Mohamad Zabri, Akmal Hakim; Mahamad, Nor Azlindamazlini (International digital organization for scientific information (IDOSI), 2016)
The purpose of this paper is to identify the level of understanding on Total Quality Management (TQM) in education sector among undergraduate students in public university in Malaysia.Random sampling technique was applied in this study whereas 299 questionnaires were distributed.Thus, all the data obtained was analyzed by using Statistical Package for Social Sciences (SPSS) version 20. From the result of mean score, the study suggested the overall of understanding on TQM practices among undergraduates were high.